Playful Teaching and Learning - Walsh, Glenda; McMillan, Dorothy; McGuinness, Carol (Los Angeles : SAGE, 2017)
Informed by international research along with contrasting perspectives on different forms of play, this book emphasises the importance of play to children, and the opportunities that play provides for learning and development.
Includes bibliographical references and index.
Keywords: Early childhood education -- Great Britain; Early childhood education -- Activity programs -- Great Britain; Play; Education